THE BALANCE OF IMPLEMENTATION BETWEEN PROJUSTITIA AND IMMIGRATION ADMINISTRATION ACTION - Budy Mulyawan; Silvester Yansen Halawa; Raden Kevin Fabio Winata (Jurnal Ilmiah Kajian Keimigrasian, 2018)
In the current era of globalization, it is very common for humans to travel between countries. The freedom of human movement to move between countries is a basic or human rights guaranteed in the constitution. This migration right is regulated in Article 28E of the 1945 Constitution (Amendment), which determines that: "Every citizen is free to choose a place to live in the territory of the country and leave it, and the right to return." But in its development more complex problems arise which forces all parties to focus their attention on solving this problem. Of course attention is focused on the immigration institution as the guardian of the state gate, meaning as a spearhead in facing and selecting foreigners who enter or monitor foreigners in Indonesia. In carrying out its own functions Immigration agents have been provided with laws that are used in carrying out their obligations. UU no. 6 of 2011 concerning immigration is the main weapon in handling the problem of foreigners who will or have entered the territory of Indonesia. The actions taken against foreigners who commit violations in Indonesia are by pro-justisia or by immigration administrative actions (TAK).